2020
DOI: 10.1038/s41598-020-59681-1
|View full text |Cite
|
Sign up to set email alerts
|

Surviving salt fluctuations: stress and recovery in Halobacterium salinarum, an extreme halophilic Archaeon

Abstract: Flow cytometry analysis of Hbt. salinarum cells structural integrity under low salt stress and high salt reactivation. The viability of stressed Hbt. salinarum cells was assessed by flow cytometry analysis 33 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 40 publications
2
20
0
Order By: Relevance
“…Cell morphology of Hbt. salinarum changes from rod-shaped to circular in the presence of low salt (49,50). Our previous work demonstrated that the ∆hpyA strain exhibits similar circularity in standard conditions (21).…”
Section: Hpya Is Important For Wild Type Growth and Morphology In Low Salinity Stress Conditionsmentioning
confidence: 95%
“…Cell morphology of Hbt. salinarum changes from rod-shaped to circular in the presence of low salt (49,50). Our previous work demonstrated that the ∆hpyA strain exhibits similar circularity in standard conditions (21).…”
Section: Hpya Is Important For Wild Type Growth and Morphology In Low Salinity Stress Conditionsmentioning
confidence: 95%
“…Therefore, suitable haloarchaeon expression systems are often necessary. Successful homologous expression of haloarchaeal proteins has been reported in halophilic archaeal hosts, such as Halobacterium salinarum ( Nomura and Harada, 1998 ; Kixmüller and Greie, 2012 ; Vauclare et al, 2020 ) and Haloferax volcanii ( Hfx. volcanii ) ( Pohlschroder and Schulze, 2019 ; Haque et al, 2020 ).…”
Section: Mining Of the Red Sea Enzyme Poolmentioning
confidence: 99%
“…On the contrary, non-halophiles do not grow in the environment containing above 0.2M (1%) NaCl, and halotolerant organisms are viable in the presence or absence of highly saline conditions, but it is not necessary for their optimal growth [5]. Moreover, halophilic and halotolerant organisms are able to adapt to a broad range of salt concentrations, occurring seasonally, annually, or irregularly in their natural environments [4,6].…”
Section: Introductionmentioning
confidence: 99%